Human cytomegalovirus detection by real-time PCR and pp65-antigen test in hematopoietic stem cell transplant recipients: a challenge in low and middle-income countries. (1st September 2013) - Breda, Giovanni; Almeida, Bernado; Carstensen, Suzana; Bonfim, Carmem M; Nogueira, Meri B; Vidal, Luine R; Almeida, Sergio M; Raboni, Sonia M
Abstract : Aim: Cytomegalovirus (CMV) infection is one of the most common complications in patients submitted to hematopoietic stem cell transplant (HSCT). Pre-emptive therapy has been indicated in patients with laboratory evidence of CMV replication. The aims of this study were to compare real-time PCR or pp65 antigen assay methodologies to detect CMV replication in HSCT patients, define a viral load threshold for initiation of pre-emptive therapy, and assess the feasibility of its implementation in hospitals of countries with low and middle income. Material and methods: Human CMV detection by real-time PCR and pp65 antigen assay was carried out in blood and plasma samples of HSCT patients collected weekly during 3 months. Pre-emptive therapy was based on CMV antigenemia results. Results: Twenty-one patients were monitored with a total of 227 samples collected; 13 (62%) patients were children. A poor correlation was observed between qualitative results, though quantitative results showed statistically significant difference, with higher viral loads detected in patients with positive antigenemia. Compared to a positive antigenemia, a cutoff value of 1067·5 copies/ml, 3·03 log10 /ml, for viral load was obtained with 100% sensitivity and 71% specificity. Conclusion: CMV real-time PCR in whole blood was suitable for monitoring HSCT patients. However, its high cost is a limiting factor, and it could be used to monitor selected patients, those with prolonged leukopenia and underweight children, and subsequently switched to pp65 antigen test. Further studies involving larger numbers of patients should be performed to confirm this statement.